Representasi Bullying dalam Film Vina: Sebelum 7 Hari (Analisis Semiotika Roland Barthes) - Adnan Aditiyana; Iin Soraya; Sari Ekowati Hadi3 (Tamilis Synex: Multidimensional Collaboration, 2024)
Film is a mass communication medium that has a big influence in conveying entertainment and educational messages. In Indonesia, horror films are very popular because of their ability to combine elements of local culture and cinematic innovation. This research analyzes the representation of bullying in the film "Vina: Prior 7 Hari" using Roland Barthes' semiotic approach which distinguishes between denotative and connotative meaning. Using a constructivist paradigm, this research aims to understand how the reality of bullying is formed and interpreted in the film. Method was analyzed qualitatively from scenes and dialogue to reveal meaning at the denotative and connotative levels. Apart from that, this research also uses three representational approaches from Stuart Hall: reflective, intentional, and constructionist. The reflective approach shows that this film reflects the reality of bullying in society, especially at school, through depictions of verbal and physical violence. The intentional approach reveals that the director deliberately uses film elements to arouse audience empathy towards victims of bullying. The construction approach emphasizes that the meaning of bullying is socially constructed through the interaction of the audience, media, and cultural context. The research results show that this film not only depicts a tragic reality, but also encourages discussion about the importance of creating an environment that is safe and free from bullying